Experimental Evaluation and Theoretical Study of Imidazolium and Benzimidazolium. Derivatives as Corrosion Inhibitors of Mild Steel in a 0.5 M H2SO4 Solution - Said,Mohamed Elhadi (2023)
Abstract (dimOHmIm)+,I- and (dimOHmBim)+,I- were investigated as a corrosion inhibitors for MS in 0.5 M H2SO4 using gravimetric, PDP and EIS techniques. Polarization curves revealed that both compounds acted as mixed-type inhibitors, and that corrosion IE% increased with their higher concentrations. The adsorption of both inhibitors onto the MS surface obeyed Langmuir’s isotherm. The compound II showed a higher corrosion IE% than that of I. The quantum chemical calculations were applied to investigate the relationship between the two azolium salts derivatives electronic properties and their corrosion IE%.